Laser Photobiomodulation for a Complex Patient with Severe Hydroxyurea-Induced Oral Ulcerations. (10th November 2016) - Cabras, Marco; Cafaro, Adriana; Gambino, Alessio; Broccoletti, Roberto; Romagnoli, Ercole; Marina, Davide; Arduino, Paolo G.
Abstract : Patients affected by polycythemia vera (PV), a myeloproliferative neoplasm characterized by an elevated red blood cell mass, are at high risk of vascular and thrombotic complications. Conventional therapeutic options aim at reducing vascular and thrombotic risk; low-dose aspirin and phlebotomy are first-line recommendations, for patients at low risk of thrombotic events, whereas cytoreductive therapy, usually hydroxyurea (HU) or interferon alpha, is recommended for high-risk patients. In the present study, we report the case of a patient with persistent oral ulcerations, possibly related to long-lasting HU treatment, firstly treated with topic and systemic corticosteroids and then more effectively with the addition of low-level laser therapy. Laser photobiomodulation has achieved pain control and has contributed to the healing of oral ulcers without any adverse effect; this has permitted a reduction in the dose of systemic corticosteroids and the suspension of the use of the topic ones, due to the long-term stability of oral health, even after the interruption of low-level laser therapy sessions.